Assessing The Compliance Of Lifestyle Modification And Metformin Versus Lifestyle Modification & Insulin In The Management Of Gestational Diabetes, Madinah, KSA (The Review of Diabetic Studies, 2025)
Background: Between October 2023 and October 2024, 147 pregnant women with GDM who received treatment at Madinah's maternity outpatient clinics participated in a retrospective cohort research. Data on demographics, medication adherence, glycemic control, and maternal-neonatal outcomes were gathered using validated questionnaires and medical records. Descriptive statistics, including frequencies and percentages, were used to analyze the data. Methods: Between October 2023 and October 2024, 147 pregnant women with GDM who received treatment at Madinah's maternity outpatient clinics participated in a retrospective cohort research. Data on demographics, medication adherence, glycemic control, and maternal-neonatal outcomes were gathered using validated questionnaires and medical records. The data was analyzed using descriptive statistics, such as percentages and frequencies. Results: Approximately half (49%) of the participants were on metformin, while 47.6% were on insulin. In total, 46.9% reported complying with the dietary advice given. Over one-third (32.7%) reported complying with the recommendations for diet and exercise. Self-monitoring of blood glucose (SMBG) was reported in 37.4% of cases and absent in 21.1% of cases. Only 32% reported tight glycemic control during the pregnancy. In addition to the high cesareans (59.2%), and 17.7% of cases were reported to have macrosomia. Most morbidities and treatment of gestational diabetes, were reported to begin in the third trimester. Conclusion: The results show deficiencies in lifestyle adherence and early diagnosis, which could restrict the best possible glucose control and lead to unfavorable pregnancy outcomes.